Kradzież karty uprawniającej do podjęcia pieniędzy z automatu bankowego art. 278 § 5 k.k. jako przykład kryminalizacji na przedpolu czynu zabronionego - Tyburcy, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In contrast to the classical theft this offense has not been partially-decriminalized. The subject of the crime cannot be a card that entitles the owner to make payment, since it constitutes “other means of payment” within the meaning of art. 115 § 9 C.C.; and as such is the subject of the theft of another person movable property Art. 278 § 1 C.C.
Keywords: kradzież; przywłaszczenie; bankomat; własność; posiadanie